Uncertainty and effectiveness of monetary policy: A bayesian Markov switching-VAR analysis - Zulquar Nain; Bandi Kamaiah (Journal of Central Banking Theory and Practice, 2020)
There is a growing body of literature examining the effectiveness of the monetary policy on the macroeconomy in different contexts for developed and developing countries. However, lately, especially after the GFC, the focus of research shifted to examine the role of uncertainty in economic activity and on the monetary policy effectiveness. Both theoretical and empirical studies suggest that uncertainty does influence monetary policy effectiveness. However, until now, empirical studies are restricted to only developed countries. To this end, the present study examines the influence of uncertainty on monetary policy effectiveness for a developing country, namely India. We applied a non-linear VAR, which allows us to examine the effect of monetary policy shocks during high and low uncertainty periods. The results exhibit that uncertainty influences the effectiveness of monetary policy shocks. We find weaker effects of the monetary policy shocks during high uncertainty regime relative to low uncertainty regime.
Keywords: E31; E32; E40; 330; Uncertainty; Monetary Policy; India